An unbalanced monocyte macrophage polarization in the bone marrow microenvironment of patients with poor graft function after allogeneic haematopoietic stem cell transplantation. (5th July 2018) - Zhao, Hong‐Yan; Lyu, Zhong‐Shi; Duan, Cai‐Wen; Song, Yang; Han, Ting‐Ting; Mo, Xiao‐Dong; Wang, Yu; Xu, Lan‐Ping; Zhang, Xiao‐Hui; Huang, Xiao‐Jun; Kong, Yuan
Summary: Poor graft function (PGF) is a severe complication of allogeneic haematopoietic stem cell transplantation (allo‐HSCT). Murine studies have demonstrated that effective haematopoiesis depends on the specific bone marrow (BM) microenvironment. Increasing evidence shows that BM macrophages (MФs), which constitute an important component of BM immune microenvironment, are indispensable for the regulation of haematopoietic stem cells (HSCs) in the BM. However, little is known about the number and function of BM MФs or whether they directly interact with HSCs in PGF patients. In the current prospective case‐control study, PGF patients showed a significant increase in classically activated inflammatory MФs (M1; 2·18 ± 0·11% vs. 0·82 ± 0·06%, P  <   0·0001), a striking reduction in alternatively activated anti‐inflammatory MФs (M2; 3·02 ± 0·31% vs. 21·89 ± 0·90%, P  <   0·0001), resulting in a markedly increased M1/M2 ratio (0·82 ± 0·06 vs. 0·06 ± 0·002; P  <   0·0001) in the BM compared with good graft function patients. Meanwhile, standard monocyte subsets were altered in PGF patients. Dysfunctional BM MФs, which were characterized by reduced proliferation, migration and phagocytosis, were evident in PGF patients. Furthermore, BM MФs from PGF patients with high tumour necrosis factor‐α and interleukin 12 levels and low transforming growth factor‐β levels, led to impaired BM CD34 + cell function. In summary, our data indicate that an unbalanced BM M1/M2 ratio and dysfunctional MФs may contribute to the occurrence of PGF following allo‐HSCT.